RELATIVE DEGREE OF SUSCEPTIBILITY AND RESISTANCE OF BRASSICA CAMPESTRIS L. GENOTYPES AGAINST APHID MYZUS PERSICAEA FIELD INVESTIGATION - Sarwar, M. (The Nucleus, 2013)
Field evaluation of twenty three Brassica campestris L. genotypes was conducted for aphid (Homoptera: Aphididae) resistance during 2008 crop season. The parameters used to assess tolerance of germplasm lines included pest population during growth season and grain yield at crop maturity. Aphids showed obvious preferences for all of the germplasm investigated; however, the evaluation for resistance to pest identified several genotypes with variable potential for tolerance and sensitivity. Estimated grain yield also varied significantly due to variable pest intensity noted, and seemed to be more appropriately dependent on the pest population conditions at the experimental site. Among the germplasm, the estimation obtained regarding both the parameters sorted out MM-II/02-3 and MM-I285 genotypes as most tolerant due to less pest infestation and damage. Peak infestations by aphid caused severe crop fatalities on S-9- S-97-0.75+75/55 and S-9-1006/95 genotypes, affecting the seed weight and resulting an immense reduction in grain produced. The degrees of aphids’ population and infestation on different Brassica genotypes appeared to be governed by means of varietals characteristics of diverse germplasms. The result of resistance test conducted under field environment is an effective and consistent approach in the practical selection of crop lines resistant or partially resistant to pests for use in future breeding programs.